Educational inequalities and success in Asian countries in PISA 2009 - Alba Castejón Company; Adrián Zancajo; Ferran Ferrer (FahrenHouse, 2011)
This article discusses the results of PISA 2009 from seven Asian countries. The analysis focuses on three hubs of educational inequality: academic inequalities, inequalities by gender and social in- equalities. The main conclusion drawn from the results of this work is that is not possible to affirm that Asian education systems constitute a homogeneous educational model.